Aspek Health Belief Model dan Kepatuhan Ibu Melakukan Kunjungan Antenatal K4 di Masa Pandemi COVID-19 - Filpin Luciami Ayuwandini Haning; Christina Olly Lada; Marylin S. Junias; Yermia Jefri Manafe; Sabina Gero (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze aspects of the Health Belief Model (HBM) with mothers' compliance with ANC K4 visits during the COVID-19 pandemic in the working area of ​​the Sikumana Health Center. The method used is quantitative with a cross-sectional design. The sampling technique uses simple random sampling. The results showed a significant relationship between maternal compliance with ANC K4 visits and the six aspects of HBM (perceived susceptibility, perceived seriousness, perceived benefit, perceived barrier, cues to action and self-efficacy). Data analysis using multiple logistic regression showed a simultaneous effect between perceived susceptibility (OR 8.315) and perceived benefit (OR 0.040) with maternal compliance with K4 antenatal visits; perceived susceptibility was the most dominant variable with p = 0.000, CI = 3.835 - 18,029. In conclusion, the HBM aspect that influences a mother's adherence to ANC visits is Perceived susceptibility. Keywords: Health Belief Model, Compliance of Pregnant Women, K4 Antenatal Visits